Pengaruh Penambahan Fitobiotik dan Lactobacillus Sp. dalam Ransum Terhadap Deposisi Lemak dan Karkas pada Kalkun - Putra, Dika Agung Nugroho; Yunianto, Vitus Dwi; Sukamto, Bambang; Krismiyanto, Lilik (Journal Galung Tropika, 2022)
The study aimed to determine the effect of adding phytobiotics derived from the skin of shallots, garlic, and bay leaves combined with Lactobacillus sp. in turkey rations on fat deposition and carcass percentage. The experimental cattle used were 80 unsex turkeys aged 3 months. The experiment was arranged in a randomized block design (RAK) with 5 treatments and 4 groups based on body weight, each containing 4 turkeys. Groups were divided based on body weight, namely K1 (400-550 g); K2 (551-700 g); K3 (701-850 g), and K4 (851-1000 g). The treatments applied were T0= Basal ration/RB; T1=RB + 0.25 g Lactobacillus sp. ; T2 = RB + 2% Phytobiotics.; T3= RB+0.25 g Lactobacillus sp.+ 2% Phytobiotics and T4= RB + 0.5 g Lactobacillus sp.+ 2% Phytobiotics. The research parameters measured included fat digestibility, the relative weight of abdominal fat, meat fat content, and carcass percentage. The data were analyzed for variance at the 5% significance level, followed by Duncan’s multiple area tests with a 5% significance level. The results showed that the addition of phytobiotics combined with Lactobacillus sp. had a significant effect (P<0.05) on the decrease in fat digestibility and fat content of meat but no significant effect (P>0.05) on the relative weight of abdominal fat and carcass percentage. The addition of 2% phytobiotics combined with 0.50 g of Lactobacillus sp. can reduce turkey meat’s fat digestibility and fat content but does not increase the relative weight of abdominal fat and carcass percentage.